Effective leadership model: Needs analysis study of leaders in higher educational institutions of majlis amanah rakyat ('MARA') - Mat, Norazizah Che; Ghani, Muhammad Faizal A.; Jaafar, Muhammad Nazri Che (Primrose Hall Publishing Group, 2019)
This study aims to identify the views of leaders in advanced higher educational institutions. The value of the Leadership Model and the importance of leaders having effective leadership qualities in higher educational institutions of Majlis Amanah Rakyat ('MARA') will also be discussed. For the purpose of achieving the objectives of this study, structured interviews were done on ten leaders in higher educational institutions of MARA. The results of the interviews conducted were supported by the results of previous studies and a set of questionnaires were developed as instruments for the first round of the Delphi method. In addition, advancing leaders in higher educational institutions must implement the characteristics of effective leadership to form an excellent institution. © 2019 Primrose Hall Publishing Group.